Impact of sedimentary processes on white-sand vegetation in an Amazonian megafan. (4th October 2016) - Cordeiro, Carlos L. O.; Rossetti, Dilce F.; Gribel, Rogério; Tuomisto, Hanna; Zani, Hiran; Ferreira, Carlos A. C.; Coelho, Luiz
Abstract: Amazonian white-sand vegetation has unique tree communities tolerant to nutrient-poor soils of interest for interpreting processes of adaptation in neotropical forests. Part of this phytophysionomy is confined to Late Quaternary megafan palaeo-landforms, thus we posit that sedimentary disturbance is the main ecological factor controlling tree distribution and structuring in this environment. In this study, we characterize the topographic trend of one megafan palaeo-landform using a digital elevation model and verify its relationship to the forest by modelling the canopy height with remote sensing data. We also compare the composition and structure (i.e. canopy height and diameter at breast height) of tree groups from the outer and inner megafan environments based on the integration of remote sensing and floristic data. The latter consist of field inventories of trees ≥ 10 cm dbh using six (500 × 20 m) plots in várzea, terra firme and igapó from the outer megafan and 20 (50 × 20 m) plots in woodlands and forests from the inner megafan. The unweighted pair group method with arithmetic mean (UPGMA) and the non-metric multidimensional scaling (NMDS) were applied for clustering and dissimilarity analyses, respectively. The megafan is a sand-dominated triangular wetland with a topographic gradient of < 15 cm km −1, being more elevated along its axis. The outer megafan has a higher number of tree species (367), taller canopy height (mean of 14.1 m) and higher diameter at breast height (mean of 18.2 cm) than the white-sand forest. The latter records 89 tree species, mean canopy height of 8.4 cm and mean diameter at breast height of 15.3 cm. Trees increase in frequency closer to channels and toward the megafan's axis. The flooded and nutrient-poor sandy megafan substrate favoured the establishment of white-sand vegetation according to the overall megafan topography and morphological heterogeneities inherent to megafan sub-environments.